Central neurogenic hyperventilation in conscious patients due to CNS neoplasm: a case report and review of the literature on treatment. Issue 5 (10th April 2020) - Neves Briard, Joel; Beaulieu, Marie-Claude; Lemoine, Émile; Beaulieu, Camille; Dubé, Bruno-Pierre; Lapointe, Sarah
Abstract: Background: Central neurogenic hyperventilation (CNH) is increasingly reported in conscious patients with a CNS neoplasm. We aimed to synthesize the available data on the treatment of this condition to guide clinicians in their approach. Methods: We describe the case of a 39-year-old conscious woman with CNH secondary to glioma brainstem infiltration for whom hyperventilation was aborted with hydromorphone, dexamethasone, and brainstem radiotherapy. We then performed a review of the literature on the treatment of CNH in conscious patients due to a CNS neoplasm. Results: A total of 31 studies reporting 33 cases fulfilled the selection criteria. The underlying neoplasm was lymphoma in 15 (45%) and glioma in 13 (39%) patients. Overall, CNH was aborted in 70% of cases. Opioids and sedatives overall seemed useful for symptom relief, but the benefit was often of short duration when the medication was administered orally or subcutaneously. Methadone and fentanyl were successful but rarely used. Chemotherapy was most effective in patients with lymphoma (89%), but not glioma (0%) or other neoplasms (0%). Patients with lymphoma (80%) and other tumors (100%) responded to radiotherapy more frequently than patients with glioma (43%). Corticosteroids were moderately effective. Subtotal surgical resection was successful in the 3 cases for which it was attempted. Conclusion: Definitive treatment of the underlying neoplasm may be more successful in aborting hyperventilation. Variable rates of palliation have been observed with opioids and sedatives. Treatment of CNH is challenging but successful in a majority of cases.